Baseline HBV‐DNA load plus AST/ALT ratio predicts prognosis of HBV‐related hepatocellular carcinoma after hepatectomy: A multicentre study. Issue 11 (18th September 2021) - Shen, Junyi; Dai, Junlong; Zhang, Yu; Xie, Fei; Yu, Yu; Li, Chuan; Wen, Tianfu
Abstract: Hepatitis B viral (HBV) load and hepatic enzymes play a critical role in hepatocellular carcinoma (HCC) development. However, the clinical significance of these in HBV‐related HCC patients after hepatectomy remains unclear. In this study, we analysed 1, 940 HBV‐related HCC patients who underwent hepatectomy from four hospitals in west China. Risk classification was constructed based on baseline HBV‐DNA load and AST/ALT ratio. Based on the HBV‐DNA load and AST/ALT ratio classification, four types with distinguishable prognoses were established. Type 1 patients had the best prognosis with 5‐year overall survival (OS) of 69.8%, followed by type 2 and type 3 patients, whereas type 4 patients had the worst prognosis with 5‐year OS of 42.7%. Similarly, the four types had statistically different recurrence‐free survival. This classification was significantly associated with HCC recurrence (hazard ratio [HR]:1.492, p < .001) and long‐term survival (HR: 1.574, p = .001). Pathologically, type 4 correlated with more advanced tumours considering tumour size and microvascular invasion than those in type 1, 2, or 3. Moreover, type 4 patients had more severe hepatic inflammation in underlying liver. Conversely, type 1 patients had an active tumour immune microenvironment as indicated by more CD8+ T cell infiltration and less PD‐L1 expression. In conclusion, the classfication based on baseline HBV‐DNA load and AST/ALT ratio could effectively stratify HBV‐related HCC patients with distinguishable prognoses after hepatectomy.